Line Spectrum Chaotification on QZS Systems with Time-Delay Control - Jing Zhang; Tao Tang; Wenhua Fang (Complexity)
Chaotification can be employed to weaken or eliminate the feature of line spectra of waterborne noise. The efficiency of this method lies on the use of small control. The analysis reveals that the critical control gain depends on the stiffness of vibration isolation systems. Thus, an isolation raft system based on quasi-zero-stiffness (QZS) property is proposed for line spectrum chaotification. A nonlinear time-delay controller is derived accordingly. Comparative analysis shows that the new approach allows much smaller control, and the intensity of line spectra is further reduced. Numerical simulations also indicate other advantages with the introduction of QZS system into chaotification.